A note on centralizers. (1st July 2000) - Bell, Howard E.
Abstract : For prime ringsR, we characterize the setU ∩ C R ( [ U, U ] ), whereU is a right ideal ofR ; and we apply our result to obtain a commutativity-or-finiteness theorem. We include extensions to semiprime rings.